Predictive Capabilities of Corotating Interaction Regions Using STEREO and Wind In‐Situ Observations - Yutian Chi; Chenglong Shen; Christopher Scott; Mengjiao Xu; Mathew Owens; Yuming Wang; Mike Lockwood (Space Weather)
Abstract Solar wind stream interaction regions (SIRs) and corotating interaction regions (CIRs) can cause geomagnetic storms and change energetic particle environment, ionospheric composition on Earth. Therefore advanced warning of SIRs/CIRs is vital for mitigating the effect of space weather on critical infrastructures in modern society. Recently, several solar missions, for example, Vigil mission (Luntama et al., 2020) and Solar Ring mission (Wang et al., 2020), that can be served as a space weather monitor, have been proposed. To evaluate the capabilities of these future missions of predicting SIRs/CIRs, the Solar Terrestrial Relations Observatory (STEREO‐B) spacecraft is used to investigate the correlation between SIRs/CIRs detected by STEREO‐B and Wind spacecraft. The correlation coefficients of solar wind velocity in SIRs/CIRs are significantly higher than that of magnetic field intensity or plasma density. It indicates that the velocity structure of solar wind is more persistent than magnetic field and ion density. By assuming the SIR/CIR structures are stable and ideal corotation, 58.9% of SIRs/CIRs in the STEREO‐B CIR catalog can be used to predict CIR arrival time in near‐Earth space. With increasing longitudinal and latitudinal separations between STEREO‐B and Wind, the percentage of accurately predicted CIRs decreases gradually from 100% to 20%. If the separation angle between STEREO‐B and Wind is within 30° in longitude and approximately ±5° in latitude, more than 93.2% of SIRs/CIRs can be accurately predicted several days in advance. This demonstrates that a spacecraft situated 30° trailing Earth in its orbit, can optimize our space weather‐predicting capabilities for the Earth and lessen the risk of missing or “false alarms” CIRs.